1995
DOI: 10.1159/000188760
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sodium Intake on Cystinuria with and without Tiopronin Treatment

Abstract: As with many other amino acids the transport of cystine across the tubular epithelium is coupled to a parallel transport of sodium. We have studied the effect of a sodium-restricted diet on the urinary excretion of cystine in 13 patients with cystinuria, 7 of whom were treated with the SH compound tiopronin (2-mercaptopropionylglycine). Five of the patients with tiopronin and 5 without were also given sodium bicarbonate. The patients were instructed to follow a sodium-restricted diet during three periods of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
(30 reference statements)
1
30
0
1
Order By: Relevance
“…136,137 Sodium restriction is advised for all patients with cystinuria because sodium and cystine excretion are associated. 138 In small studies, sodium restriction significantly decreased cystine excretion, [138][139][140] reflecting this coupling of cystine to parallel sodium transport in the kidney. Elevated dietary protein is associated with increased urinary cystine 141 and a reduction in overall protein intake can decrease urinary cystine levels.…”
Section: Index Patient 4: Cystine Stonementioning
confidence: 97%
“…136,137 Sodium restriction is advised for all patients with cystinuria because sodium and cystine excretion are associated. 138 In small studies, sodium restriction significantly decreased cystine excretion, [138][139][140] reflecting this coupling of cystine to parallel sodium transport in the kidney. Elevated dietary protein is associated with increased urinary cystine 141 and a reduction in overall protein intake can decrease urinary cystine levels.…”
Section: Index Patient 4: Cystine Stonementioning
confidence: 97%
“…38,39,41 Traditionally, night was thought to be when most patients were at highest risk of cystine supersaturation. 42 However, studies have not shown a diurnal difference in the number of discrete super saturation episodes. 43 We ask our patients to complete a diary describing fluid intake and our special ist dietician provides tailored advice regarding fluid manage ment depending on each patient's individ ual circum stances.…”
Section: Hydrationmentioning
confidence: 99%
“…14,42,47 Lowering sodium intake by 3.5 g per day decreases cystine excretion by 156 mg per day, which might maintain soluble cystine levels in the patient. 48 In the UK, the average salt intake per day is 8.6 g (3.4 g sodium), and 75% of this salt intake comes from processed foods.…”
Section: Hydrationmentioning
confidence: 99%
“…The most common way of alkalization that is otherwise used today is administration of potassium citrate. An increased urine pH can be also accomplished by sodium bicarbonate, but the additional load of sodium with this form of alkalization might have negative effects due to increased excretion of cystine [34].…”
Section: Aspects Of the Medical Treatmentmentioning
confidence: 99%